The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1111/ele.13786
|View full text |Cite
|
Sign up to set email alerts
|

Historical decrease in agricultural landscape diversity is associated with shifts in bumble bee species occurrence

Abstract: Agricultural intensification is a key suspect among putative drivers of recent insect declines, but an explicit link between historical change in agricultural land cover and insect occurrence is lacking. Determining whether agriculture impacts beneficial insects (e.g. pollinators), is crucial to enhancing agricultural sustainability. Here, we combine large spatiotemporal sets of historical bumble bee and agricultural records to show that increasing cropland extent and decreasing crop richness were associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
56
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 74 publications
2
56
0
Order By: Relevance
“…By contrast, work done in North America and Europe showed that species are failing to track warming at northern range limits and experiencing range losses at southern range limits [16]. Studies looking at North American bumblebee relative abundances have largely found declines, and are generally consistent with our estimates of declines [7,8,11,13].…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…By contrast, work done in North America and Europe showed that species are failing to track warming at northern range limits and experiencing range losses at southern range limits [16]. Studies looking at North American bumblebee relative abundances have largely found declines, and are generally consistent with our estimates of declines [7,8,11,13].…”
Section: Discussionsupporting
confidence: 81%
“…Effects of land use on bumblebee occurrence have been difficult to quantify, particularly at this large scale, and here we show that floral resources might not be the ideal metric. For example, Hemberger et al [11] found that crop diversity, rather than crop extent, was a better predictor of changes in bumblebee occurrence and McArt et al [46] found that fungicide usage was a better predictor of bumblebee decline than land use. Lastly, our floral abundance metric was developed with all bee guilds in mind [35] and, thus, may not be appropriate for bumblebees.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a mixed diet of complementary foods has been shown to be beneficial for several generalist predators and is actively sought by them (Soares et al 2004;Raubenheimer et al 2007;Harwood et al 2009;Marques et al 2015;Stowe et al 2021a). As such, landscapes with fewer diversity of crops or landscape diversity may manifest as decreases in the physiological condition of mobile predatory arthropods such as lady beetles, leading to longer-term population declines, as has been found for other beneficial insects (Hemberger et al 2021).…”
Section: Discussionmentioning
confidence: 99%